Wireless Multichannel Multipoint Broadcast Service for Mobile Stations - B. Homer Benny; K. Chaitanya Deepti; P. Ratna Kumar (Universitas Islam Sultan Agung, 2013)
In wireless Multicast Broadcast Service (MBS), the common channel is used to multicast the MBS content to the Mobile Stations (MSs) on the MBS calls within the coverage area of a Base Station (BS), which causes interference to the dedicated channels serving the traditional calls, and degrades the system capacity. The MBS zone technology is proposed in Mobile Communications Network (MCN) standards to improve system capacity and reduce the handoff delay for the wireless MBS calls. In the MBS zone technology, a group of BSs form an MBS zone, where the macro diversity is applied in the MS, the BSs synchronize to transmit the MBS content on the same common channel, interference caused by the common channel is reduced, and the MBS MSs need not perform handoff while moving between the BSs in the same MBS zone. However, when there is no MBS MS in a BS with the MBS zone technology, the transmission on the common channel wastes the bandwidth of the BS. It is an important issue to determine the condition for the MBS Controller (MBSC) to enable the MBS zone technology by considering the Quality of Services (QoS) for traditional calls and MBS calls are used to reduce the dependency over the common channel and also it is going to reduce the delay over the network. By enabling Dynamic Channel Allocation (DCA) and Enhance Dynamic Channel Allocation (EDCA) we are going to overcome these problems.